2006
DOI: 10.1590/s0004-27492006000300022
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography in presumed subretinal Toxocara granuloma: case report

Abstract: Our aim was to study optical coherence tomographic findings in a case of Toxocara granuloma. A patient with a cicatricial macular lesion, diagnosed as ocular toxocariasis, was examined with optical coherence tomography. In optical coherence tomography images, the macular granuloma appeared as a highly reflective round mass protruding above the retinal pigment epithelium with two other surrounding masses. Optical coherence tomography may increase understanding of the pathophysiology of the retinal Toxocara gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…According to a review paper by Arevalo et al (96), three major clinical types of OT syndrome have been suggested, based on the severity of manifestations, including diffuse nematode endophthalmitis, the peripheral inflammatory mass type, and the posterior pole granuloma type (100)(101)(102). In general, patients with OT have a normal white blood count, normal serum IgE level, and no eosinophilia (96).…”
Section: Ocular Toxocariasismentioning
confidence: 99%
See 2 more Smart Citations
“…According to a review paper by Arevalo et al (96), three major clinical types of OT syndrome have been suggested, based on the severity of manifestations, including diffuse nematode endophthalmitis, the peripheral inflammatory mass type, and the posterior pole granuloma type (100)(101)(102). In general, patients with OT have a normal white blood count, normal serum IgE level, and no eosinophilia (96).…”
Section: Ocular Toxocariasismentioning
confidence: 99%
“…In general, patients with OT have a normal white blood count, normal serum IgE level, and no eosinophilia (96). Substantial clinical evidence indicates that the most common presentation of OT is a granuloma found in the peripheral retina, seen in 50% to 64% of cases, with a posterior pole granuloma seen in 25% to 36% of cases and endophthalmitis seen in Ͻ25% of cases (102,103). Over 50% of cases are unilateral ocular infections presenting with mild ocular inflammation, but if the infection is persistent, bilateral disease may be manifested (104).…”
Section: Ocular Toxocariasismentioning
confidence: 99%
See 1 more Smart Citation
“…This study was performed at the Department of Ophthalmology, Xinhua Hospital, which is affiliated to Shanghai Jiaotong University School of Medicine. Fundoscopy, immunological testing, and imaging methods were used to diagnose ocular toxocariasis in these children [14]. With the help of fundoscopy, ophthalmologists usually detect the following signs: inflammatory mass, a peripheral or posterior granuloma, and vitreous strands [15].…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Histological examinations of Toxocara granulomas in monkeys were also found to be nodular with fibrous capsules. 4 The mass in this study has a similarly nodular appearance and is associated with a hyperreflective fibrotic cap on OCT, though it was not associated with fluid.…”
mentioning
confidence: 96%